Transforming Health Care One Team at a Time: Ten Observations and the Trail Ahead. Issue 3 (June 2018) - Salas, Eduardo; Zajac, Stephanie; Marlow, Shannon L.
The present review synthesizes existing evidence and theory on the science of health care teams and health care team training. Ten observations are presented that capture the current state of the science, with applications to both researchers and practitioners. The observations are drawn from a variety of salient sources, including meta-analytic evidence, reviews of health care team training, primary investigations, and the authors' collective expertise in developing and implementing medical team training. These observations provide insight into the team (e.g., psychological safety) and organizational-level (e.g., culture for teamwork) factors that drive effective health care teamwork, as well as advancements and best practices for designing and implementing team training initiatives (e.g., multilevel measurement). We highlight areas where new knowledge has emerged, and offer directions for future research that will continue to improve our understanding of health care teams in the future.